Cloning of the extra sex combs gene of Drosophila and its identification by P-element mediated gene transfer. - Frei, E.; Baumgartner, S.; Edstrom, J.E.; Noll, M. (The EMBO Journal, 1985)
A large region containing the extra sex combs (esc) gene of Drosophila has been cloned by microdissection from polytene chromosomes and chromosomal walking. Within this DNA, the segment comprising the esc gene has been narrowed down in several steps. First, a deletion of the esc gene, Df(2L)esc, defined a region of 380 kb. Then, a duplication carrying the esc gene, Dp(2;2)GYL, and a deletion not eliminating esc, Df(2L)prd, further reduced this region to 160 kb. Finally, because esc transcripts are expected to be present in follicles but absent in adult males, mapping of follicle and adult male transcripts limited the esc region to 10 kb. Rigorous proof that this DNA contained the esc gene was obtained by P-element-mediated transformation. We conclude that the 12 kb of DNA used for transformation include the esc gene as well as all flanking sequences required for its proper regulation in the female germ line.